Adoption of Tef (Eragrostis Tef) Production Technology Packages in Northwest Ethiopia - Atrsaw Anteneh Mihretie; Azanaw Abebe; Girmachew Siraw Misganaw (Cogent Economics & Finance, 2022)
Adoption of Tef production technology has paramount importance to increase Tef productivity, foster food security, and secure the well-being of smallholder farmers. Hence, this study aims to identify the determinants of adoption of Tef technology packages in Yilmana Densa district, and subsequently assess the factors influencing the intensity of adoption of the technology. In this study, 224 sample households were selected using systematic random sampling techniques. The data were obtained mainly from sampled Tef grower households via structured interviews, and it was supported by key informant interviews. Descriptive statistics such as Chi-square, t-test, and one-way ANOVA were employed. First-hurdle of double hurdle model result revealed that adoption decision of Tef technology packages was determined via the frequency of extension contact, agricultural training, farmers' perception, and farmers' cooperative membership, positively. The second-hurdle result also shown that the adoption intensity of Tef technology packages was influenced by the frequency of extension contact, agricultural training, demonstration participation, and seed multiplication membership, positively, whereas the distance to input market and land fragmentation influenced negatively. Therefore, efforts to be expected from the Ministry of Agriculture, extension agents, and other stockholders to enhance the adoption level of farmers.
Keywords: 330; Adoption; double-hurdle; intensity; technology; Tef